Pharyngeal-cervical-brachial variant of Guillain-Barre syndrome. - Wakerley, B; Yuki, N (2014)
The pharyngeal-cervical-brachial (PCB) variant of Guillain-Barré syndrome is defined by rapidly progressive oropharyngeal and cervicobrachial weakness associated with areflexia in the upper limbs. Serial nerve conduction studies suggest that PCB represents a localised subtype of Guillain-Barré syndrome characterised by axonal rather than demyelinating neuropathy. Many neurologists are unfamiliar with PCB, which is often misdiagnosed as brainstem stroke, myasthenia gravis or botulism. The presence of additional ophthalmoplegia and ataxia indicates overlap with Fisher syndrome. Half of patients with PCB carry IgG anti-GT1a antibodies which often cross-react with GQ1b, whereas most patients with Fisher syndrome carry IgG anti-GQ1b antibodies which always cross-react with GT1a. Significant overlap between the clinical and serological profiles of these patients supports the view that PCB and Fisher syndrome form a continuous spectrum. In this review, we highlight the clinical features of PCB and outline new diagnostic criteria.